Disciplining Interdisciplinarity: Integration and Implementation Sciences for Researching Complex Real-World Problems - Bammer, Gabriele (ANU Press, 2013)
This book provides collaborative research teams with a systematic approach for addressing complex real-world problems like widespread poverty, global